The Challenges Faced By Indian Craft Workers In Andhra Pradesh (Journal of Namibian Studies : History Politics Culture, 2023)
Andhra Pradesh, as well as India as a whole, is home to many handicrafts, each of which tells a unique story about the state’s history, cultural practices, and artistic prowess. The paper addresses the challenges artisans face. Firstly, the paper discusses the socio-economic implications of handcrafts in India, as they represent a prominent avenue for employment, particularly for rural women and marginalized segments of the population. Secondly, it addresses the environmental and sustainability considerations. Thirdly, it discusses how the craft industry contributes to the growth of the tourism sector of the state. Finally, it focuses on leather puppetry.